FATIGUE CRACK GROWTH PERFORMANCE OF TI-6AL-4V TITANIUM ALLOY BY SELECTIVE LASER MELTING - ZHANG HaiYing; LI Gang; ZANG WeiFeng; LIAO JiangHai; DONG DengKe (Jixie qiangdu, 2023)
Compact tension specimens were fabricated with Ti-6Al-4V titanium alloy by selective laser melting. Some specimens were heat treated and some were hot-isostatic pressed (HIPed). Half of these specimens in three conditions were polished. Fatigue crack growth (FCG) test was conducted to obtain FCG data, and to research into the effect of post-processes. The microstructure and fractography were observed to find possible reasons for FCG variaton. The results indicated that, FCG preformance of as-built SLM Ti-6Al-4V is inferior to conventional material due to the fine needle martensitic structure and large residual stress. Both heat treatment and hot-isostatic pressing lead to thicker o phase and more ß phase, diminsh or even eliminate the residual stress, and improve FCG performance signifcantly. FCG rates of heat treated and HIPed speicmens are comparable to those of Ti-6Al-4V fabricated by conventional techonology. When the crack length and stress intensity factor are larger than a certain value, surface polishing shows haldly any effect.